Quantitative PCR assays to detect whales, rockfish, and common murre environmental DNA in marine water samples of the Northeastern Pacific. - Elizabeth A Andruszkiewicz; Kevan M Yamahara; Collin J Closek; Alexandria B Boehm (PLoS ONE, 2020)
Monitoring aquatic species by identification of environmental DNA (eDNA) is becoming more common. To obtain quantitative eDNA datasets for individual species, organism-specific quantitative PCR (qPCR) assays are required. Here, we present detailed methodology of qPCR assay design and testing, including in silico, in vitro, and in vivo testing, and comment on the challenges associated with assay design and performance. We use the presented methodology to design assays for three important marine organisms common in the California Current Ecosystem (CCE): humpback whale (Megaptera novaeangliae), shortbelly rockfish (Sebastes jordani), and common murre (Uria aalge). All three assays have excellent sensitivity and high efficiencies ranging from 92% to 99%. However, specificities of the assays varied from species-specific in the case of common murre, genus-specific for the shortbelly rockfish assay, and broadly whale-specific for the humpback whale assay, which cross-amplified with other two other whale species, including one in a different family. All assays detected their associated targets in complex environmental water samples.